Importance of confirmatory test characteristics in optimizing community-based screening for tuberculosis: an epidemiological modeling analysis - Brümmer, Lukas E.; Ryckman, Theresa S.; Shrestha, Sourya; Marx, Florian; Worodria, William; Christopher, Devasahayam J.; Theron, Grant; Cattamanchi, Adithya; Denkinger, Claudia M.; Dowdy, David W.; Kendall, Emily A. (BMC infectious diseases, 2025)
Background: The costs, operational barriers, and sensitivity of available tools to confirm a TB diagnosis limit current active case-finding (ACF) efforts for tuberculosis (TB). However, it is not well understood which of these limitations have the greatest epidemiological relevance and might therefore warrant prioritization in confirmatory test development. Methods: To explore which features of the confirmatory testing step most influence the impact of ACF, we developed a state-transition model of a one-time, community-based ACF campaign, with a fixed budget of one million United States dollars for screening and confirmatory testing, assuming an adult target population with four times the national prevalence of Uganda. We compared TB diagnoses, mortality, and transmission when conducting ACF with a currently available confirmatory test (mirroring sputum-based Xpert Ultra) versus ACF with an improved confirmatory test, i.e., (1) increased sensitivity (from 69% to 80%), (2) non-sputum specimen type (increasing specimen availability from 93% to 100%), (3) immediate turn-around of test results at the point-of-care (increasing delivery of positive results from 91% to 100%), or (4) reduced costs (from $20 to $10 per confirmatory test). Results: In a simulated target population of 500,000 adults, 8,029 (1.6%; 95% uncertainty range [UR] 6,634-9,380) had TB disease, and 1,136 (789-1,586) were projected to die of TB in the absence of ACF. Assuming current tests, ACF could reach 149,811 (90,834 − 217,928; 30% of the target population) people under the allotted budget, connecting 1,151 (676-1,813) individuals with TB to treatment and averting 135 (64–249) deaths. Higher diagnostic sensitivity most increased the number of people with TB who received treatment as a result of ACF (by 15% [5-27%]). However, improvements that could benefit individuals regardless of their sputum bacillary load, such as reduced test costs, achieved larger reductions in mortality (11% [4-36%]). Conclusion: Due to greater detection of individuals with high bacillary load, making confirmatory tests for community-based TB screening less expensive and more accessible may lead to greater population health benefits than further increasing test sensitivity. Nonetheless, achieving large (> 20%) increases in the health impact of ACF will require improvements to components of ACF other than the confirmatory diagnostic test.
Veröffentlicht: 27. Oktober 2025
Gesehen am 10.12.2025